Enhancing efficiency and precision in CRISPR genome editing for plants using computational tools: ENHANCING EFFICIENCY AND PRECISION IN CRISPR GENOME EDITING FOR COMPUTATIONAL TOOLS - MEGHA S SOGALAD; USHAKIRAN B; V DINESH KUMAR (Journal of Oilseeds Research, 2024)
Integrating computational tools into CRISPR-Cas9 genome editing has significantly enhanced the precision and efficiency of plant genetic modifications. This review explores bioinformatics resources’ development, functionality, and application in designing, optimizing, and analyzing CRISPR-based experiments. From initial discoveries of CRISPR arrays to their evolution as powerful gene-editing technologies, computational advancements have played a pivotal role in predicting guideRNA(gRNA) efficiency, minimizing off-target effects, and streamlining editing processes. This article highlights key web-based platforms, such as CHOPCHOP, CRISPOR, CRISPR-P, Benchling, and Deskgen, comparing their features for gRNA design and off-target prediction. Tools like TIDE and TIDER for downstream analysis for evaluating editing outcomes are also discussed. By leveraging bioinformatics, researchers can overcome the complexities of plant genomes, enhance experimental accuracy, and accelerate crop improvement initiatives. This review underscores the transformative impact of computational tools in improving the efficiency of CRISPR-Cas mediated genome editing technologies for sustainable agriculture.